2009
DOI: 10.1111/j.1468-1331.2008.02500.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the menstrual cycle influence the motor and phosphene thresholds in migraine?

Abstract: The results imply that PTs and RMTs can be reliably measured independently from the menstrual hormone status in female migraineurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…The exact generation of phosphene perception is still under discussion, results suggest that PTs are not functionally analogous to motor-evoked potentials following TMS over M1 but more to conscious perception of visual stimuli, nevertheless occurring within an earlier time window [52]. Unfortunately, it was not possible to measure the cortical excitability in the different phases of the menstrual cycle of the patients, therefore we could not evaluate if the fluctuation of PTs [3,14] was eventually reduced by the stimulation.…”
Section: Discussionmentioning
confidence: 75%
“…The exact generation of phosphene perception is still under discussion, results suggest that PTs are not functionally analogous to motor-evoked potentials following TMS over M1 but more to conscious perception of visual stimuli, nevertheless occurring within an earlier time window [52]. Unfortunately, it was not possible to measure the cortical excitability in the different phases of the menstrual cycle of the patients, therefore we could not evaluate if the fluctuation of PTs [3,14] was eventually reduced by the stimulation.…”
Section: Discussionmentioning
confidence: 75%
“…All experiments were performed at the same phase of the menstrual cycle, or in active dosage and withdrawal phases in each subject taking low dosage oral contraceptives, because previous studies showed that, even though MT are unchanged by hormonal levels in both MP and CS, there are differences in SICI measured in the follicular phase compared to the luteal phase in CS [24, 25]. …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the ovarian cycle may represent another factor influencing cortical excitability [45, 46]; only four studies explicitly assessed such a variable [32, 33, 35, 38], whose effect on cortical excitability is nevertheless still matter of debate [47, 48]. …”
Section: Exploration Of Heterogeneitymentioning
confidence: 99%